CD73 regulates vascular smooth muscle cell functions and facilitates atherosclerotic plaque formation. Issue 11 (27th October 2015) - Yang, Jiayin; Jian, Rongrong; Yu, Jiangang; Zhi, Xiuling; Liao, Xiaohong; Yu, Jerry; Zhou, Ping
Abstract: Extracellular adenosine, generated by ecto‐5′‐nucleotidase (CD73) via enzymatic catalyzation, has been found to facilitate atherosclerosis (AS). Thus, suppressing CD73 may attenuate AS. In this study, we evaluated the role of CD73 during AS development and further explored cellular and molecular mechanism in smooth muscle cells (SMCs). In a mouse model of carotid artery ligation, inactivation of CD73 inhibited migration and proliferation of vascular SMCs. In in vitro experiments, RNA interference of CD73 inhibited migration, proliferation, and foam cell transformation of human umbilical artery smooth muscle cells. Further, we established an atherosclerotic model using ApoE−/− mice fed with a western diet for 16 weeks. Inactivation of CD73‐attenuated AS and hyperlipidemia in ApoE−/− mice. In conclusion, our data suggest that CD73 facilitates AS by promoting migration, proliferation, and foam cell transformation of vascular SMCs and elevating serum lipid levels. Thus, inhibition of CD73 may be beneficial for prevention and treatment of AS. © 2015 IUBMB Life, 67(11):853–860, 2015